Credit risk transfer and de facto GSE reform - David L. Finkelstein; Andreas Strzodka; James Vickery (Federal Reserve Bank of New York, 2018)
We summarize and evaluate Fannie Mae and Freddie Mac's credit risk transfer (CRT) programs, which have been used since 2013 to shift a portion of credit risk on more than 1.8 trillion of mortgages to private sector investors. We argue that the CRT programs have been successful in reducing the exposure of the federal government to mortgage credit risk without disrupting the liquidity or stability of mortgage secondary markets. In the process, the programs have created a new financial market for pricing and trading mortgage credit risk, which has grown in size and liquidity over time. The CRT programs provide an important building block to help facilitate reform of the U.S. housing finance system.
Keywords: G10; G18; G21; G23; G28; 330; mortgage; credit risk transfer; securitization; Fannie Mae; Freddie Mac; GSE